2018
DOI: 10.1111/gcb.14391
|View full text |Cite
|
Sign up to set email alerts
|

Feasting on terrestrial organic matter: Dining in a dark lake changes microbial decomposition

Abstract: Boreal lakes are major components of the global carbon cycle, partly because of sediment‐bound heterotrophic microorganisms that decompose within‐lake and terrestrially derived organic matter (t‐OM). The ability for sediment bacteria to break down and alter t‐OM may depend on environmental characteristics and community composition. However, the connection between these two potential drivers of decomposition is poorly understood. We tested how bacterial activity changed along experimental gradients in the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 111 publications
1
27
0
Order By: Relevance
“…Although divergence rates did not differ between lakes, changes more closely tracked humification and pH of sediment pore water. These results advance previous studies that have shown both sediment pH and humification influence microbial community composition at single time points (Ruiz‐González et al ; Amaral et al ; Fitch et al ; Tripathi et al ). One explanation for the importance of humic substances is that they may provide favorable conditions for microbial growth by acting both as electron donors and acceptors (Hessen ; Lovley et al ; Torres et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Although divergence rates did not differ between lakes, changes more closely tracked humification and pH of sediment pore water. These results advance previous studies that have shown both sediment pH and humification influence microbial community composition at single time points (Ruiz‐González et al ; Amaral et al ; Fitch et al ; Tripathi et al ). One explanation for the importance of humic substances is that they may provide favorable conditions for microbial growth by acting both as electron donors and acceptors (Hessen ; Lovley et al ; Torres et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Our observations of an increasingly humic signal over time are consistent with observations of successive microbial processing to a diverse, "universal" aquatic DOM pool 50,51 as well as "universal" fluorescent signatures, consistent with similar functional processing of material by microbes to a convergent optical signature regardless of source 52 . Microbial community structure and function appear to play a role in this process, illustrated by the differences in production of humic fluorescence between size-fractionated inocula and the role of UV exposure in accelerating production of humic material 9,53 . Our results illustrate that optical signatures for DOM carry a microbial processing signature that skews toward humic-like fluorescence that www.nature.com/scientificreports/ is more distributed in excitation-emission space than precursor DOM, consistent with a DOM pool diversified by microbes, where structurally diverse fluorescent molecules do not directly overlap.…”
Section: Microbial Size Dependency Of Dom Diagenesis Microbial Transformations Of Dom Resulted In Threementioning
confidence: 99%
“…Our results suggest that the close molecular-level association between DOM and microbes can result in chemodiversity influencing ecosystem functioning. Different microbial communities have affinities for different carbon compounds (15,53), partly because they have different functional genes for degrading macromolecules (54). These preferences would explain how a greater diversity of organic molecules provides more niches for microbes to occupy (8,9) and increases carbon mineralization.…”
Section: Discussionmentioning
confidence: 99%